Prevalence and clinical significance of koala retrovirus in two South Australian koala (Phascolarctos cinereus) populations. Issue 7 (4th June 2019) - Fabijan, Jessica; Miller, Darren; Olagoke, Olusola; Woolford, Lucy; Boardman, Wayne; Timms, Peter; Polkinghorne, Adam; Simmons, Greg; Hemmatzadeh, Farhid; Trott, Darren J.; Speight, K. Natasha
Abstract : Purpose . Koala retrovirus (KoRV-A) is 100 % prevalent in northern Australian (Queensland and New South Wales) koala populations, where KoRV-B has been associated with Chlamydia pecorum disease and the development of lymphosarcoma. In southern populations (Victoria and South Australia), KoRV-A is less prevalent and KoRV-B has not been detected in Victoria, while the current prevalence in South Australian populations is unknown but is thought to be low. This study aimed to determine (i) the prevalence of KoRV in the two largest South Australian koala populations [Kangaroo Island (KI) and Mount Lofty Ranges (MLR)], (ii) KoRV subtype and (iii) if an association between KoRV and C. pecorum exists. Methodology . Wild koalas were sampled in KI ( n =170) between 2014 and 2017 and in MLR ( n =75) in 2016. Clinical examinations were performed, with blood collected for KoRV detection and typing by PCR. Results . KoRV prevalence was 42.4 % [72/170, 95 % confidence interval (CI): 34.9–49.8 %] in KI and 65.3 % (49/75, 95 % CI: 54.6–76.1 %) in MLR. Only KoRV-A, and not KoRV-B, was detected in both populations. In MLR, there was no statistical association between KoRV and C. pecorum infection ( P =0.740), or KoRV and C. pecorum disease status ( P =0.274), although KoRV-infected koalas were more likely to present with overt C. pecorum disease than subclinical infection (odds ratio: 3.15, 95 % CI: 0.91–5.39). Conclusion . KoRV-A is a prevalent pathogen in wild South Australian koala populations. Future studies should continue to investigate KoRV and C. pecorum associations, as the relationship is likely to be complex and to differ between the northern and southern populations.